How Can Environment Influence Ultra-Long Radio Propagation? - S. Mikhailov, M; A. Volkova, A; A. Permyakov, V (International Journal of Engineering and Technology, 2018)
Even a small deviation of the environmental parameter can lead to significant changes in the propagation over long distances. The article investigates the radio propagation above the sea, taking into account the distortion of the refractive index caused by evaporation. This feature of the troposphere is called the evaporation duct. The radio propagation over-the-horizon in the evaporation duct is possible. The conditions for optimal excitation of the evaporation duct by a highly directional antenna are studied. The main factors influencing the range of the radio link are studied, such as the height of the transmitting antenna and attenuation in air and in hydrometeors and diffraction at sea waves. Also, the effect of vertical variations the evaporation duct on radio propagation is considered. In addition, elevated-surface duct may appear over the sea surface separately or together with the evaporation duct. The effect of an elevated surface and mixed ducts on the radio propagation is considered. The radio propagation is calculated by the parabolic equation method.Â